2000
DOI: 10.1097/00008571-200008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of CYP2D6, CYP1A1, GSTM1 and p53 genes in a unique Siberian population of Tundra Nentsi

Abstract: The purpose of this study was to establish the frequencies of CYP2D6, CYP1A1, GSTM1 and p53 polymorphic genotypes in Tundra Nentsi, which comprises the small group of indigenous people belonging to Northern Mongoloids and Caucasians of Western Siberia. A total number of 102 Tundra Nentsi individuals and 96 Caucasians of Western Siberia were genotyped by means of polymerase chain reaction-based assays. Mutated alleles comprising CYP2D6*4, CYP1A1Val, GSTM1*0 and p53Pro were analysed along with the wild-type alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
4
1
2
Order By: Relevance
“…Frequencies of the CYP2D6*4 allele have intermediate values between those for Mongoloids of China and Russians of Siberia. A similar conclusion was made during the investigation of the sample of Tundra Nenets (102 individuals) (Duzhak et al, 2000). The frequency of CYP2D6*4 in studied sample of Russians of Siberia is consistent with the data obtained for the sample of Russians (N = 290) who live in the Cauca soid part of Russia (Voronezh oblast) (18.2%; p = 0.73) and in Estonia (14.4%; p = 0.35), as well as for the European German sample (20.7%; p = 0.15) (Sachse et al, 1997;Marandi et al, 1997;Gaikovitch et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Frequencies of the CYP2D6*4 allele have intermediate values between those for Mongoloids of China and Russians of Siberia. A similar conclusion was made during the investigation of the sample of Tundra Nenets (102 individuals) (Duzhak et al, 2000). The frequency of CYP2D6*4 in studied sample of Russians of Siberia is consistent with the data obtained for the sample of Russians (N = 290) who live in the Cauca soid part of Russia (Voronezh oblast) (18.2%; p = 0.73) and in Estonia (14.4%; p = 0.35), as well as for the European German sample (20.7%; p = 0.15) (Sachse et al, 1997;Marandi et al, 1997;Gaikovitch et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…According to the literature data, in the related (by language) to the Forest Nenets population of Sam burg Tundra Nenets, approximately the same fre quency of GSTM1 0/0 (39.8%; p = 0.71) was recorded in the sample of 102 practically healthy individuals (Duzhak et al, 2000). However, among Tundra Nenets with cancer or chromosome anomalies (N = 28), the frequency of the "null" GSTM1 0/0 genotype was (Duzhak et al, 2001). Thus, an association between the presence of the mutant "null" GSTM1 0/0 genotype and the risk of the development of cancer was demonstrated for the first time in Samoyedic ethnic groups.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Tatars and Bashkirs, ethnic groups living in the European part of Russia, have frequencies of CYP2C9*2 of 5.1% and 6%, CYP2C9*3 of 5.4% and 6.2%, and CYP2D6*4 of 9.5% and 7.1%, respectively 16,17. The Nenets have a frequency of CYP2D6*4 of 7.3% 18. However, we do not have any pharmacogenetic data for many ethnic groups in Russia, and we do not have such data for the Nanai people.…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms are not common among Caucasians or Africans but are more frequent in Asians [Hayashi et al 1991;Shields et al 1993;Cascorbi et al 1996;Garte et al 1996;Masimirembwa et al 1998]. The highest frequencies found for these alleles in non-Amerindian populations are 0.33 for *2A in Japanese [Aynacioglu et al 1998] and 0.35 for *2C in Siberians [Duzhak et al 2000] which are still much lower than those observed for the Amerindians. The frequency of the *2C allele has also been investigated in different Brazilian cities as shown in Table 1.…”
Section: Cyp1a1mentioning
confidence: 98%